Embedded system design and code generation by using the DSL and T4 - Hưởng, Phạm Văn; Bình, Nguyễn Ngọc (Journal of Computer Science and Cybernetics, 2012)
In the development trend of embedded technology, the methods of embedded system design are studied and widely utilized. This paper presents a new approach to design embedded system and generate code from models based on Domain Specific Language and Text Template Transformation Toolkit. We define three Domain Specific Languages, build the corresponding meta-models and develop our framework. The framework is to design the models of embedded system such as the architectural model and the component model. It is also to design the flow chart of embedded software. Based on the designed models, we apply the Text Template Transformation Toolkit to generate code from models automatically